RAJGIR AN IMPORTANT PLACE OF BUDDHA CHARIKA - Susmita; kumar, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rajgir, historically known as Rajagaha, is a significant pilgrimage destination for Buddhists, symbolizing key moments in the Buddha’s life and the spread of Buddhism. The ancient city, nestled among hills, played a crucial role in Buddhist history, being the location where the Buddha delivered several important teachings, including the Lotus Sutra, and where the First Buddhist Council was held after his passing. Rajgir’s spiritual importance extends beyond its historical relevance, offering pilgrims a contemplative journey through the Buddha’s teachings of compassion, mindfulness, and the path to liberation from suffering. The city’s sites, such as Gridhakuta Hill and the Saptaparni Cave, allow pilgrims to immerse themselves in the foundational moments of Buddhism while reflecting on their own spiritual progress.Additionally, the concept of Dhammacharika, individuals who embody and propagate the Dhamma, has deep roots in Rajgir. Historically, Dhammacharikā from Rajgir were instrumental in spreading Buddhism, transforming it from a local Indian movement to a global religion. In contemporary terms, a Dhammacharika continues this role, serving as a guide and example for others by living ethically according to Buddhist principles, fostering both personal transformation and the active promotion of the Buddha’s teachings. Rajgir, therefore, remains a profound spiritual center, embodying the essence of Buddhist pilgrimage and practice.